2008
DOI: 10.1590/s0100-879x2008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Thigmotactic responses in an open-field

Abstract: The goal of the present study was to investigate the role of thigmotaxis (the tendency to remain close to vertical surfaces) in rat exploratory behavior in an open-field. Thigmotaxis was investigated in a parametric way, using 24 experimentally adult naive male Wistar rats (210-230 g). Exploratory behavior was studied in an open-field (N = 12) in 5-min sessions and behavior was analyzed in terms of where it occurred: in areas surrounded by two, one, or no walls. Another group of rats (N = 12) was studied in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 16 publications
7
62
0
13
Order By: Relevance
“…In this study, no significant differences were found in these parameters between the 388 control and treated animals (15 and 30X).In addition, the open field model is based on 389 rodent aversion to open spaces and a tendency to walk close to walls, a behaviour 390 known as thigmotaxis (Lamprea et al, 2008), allowing the assessment of the potential 391 stimulant, depressant or anxiolytic effects of a given compound (Prut and Belzung, 392 2003).Parenteral administration of 5HT 1A agonists generally induces anxiolytic-like 393 effects in rats subject to the open field tests, although non-specific 5-HT agonists (such 394 as DMT) were anxiogenic or had no effect in most studies (Prut and Belzung, 2003). In 395 our study, fluoxetine and ayahuasca-treated rats clearlyshowed a decrease in locomotion 396 activity, and less exploring behaviourthan controls, shown by decreasing rearing and 397 grooming (only ayahuasca groups).Fluoxetine is one of the most widely prescribed 398 antidepressant drugs worldwide, and is also approved for other mood disorders, 399 including generalized anxiety (Zou et al, 2013).…”
Section: Behaviour Tests 299mentioning
confidence: 68%
“…In this study, no significant differences were found in these parameters between the 388 control and treated animals (15 and 30X).In addition, the open field model is based on 389 rodent aversion to open spaces and a tendency to walk close to walls, a behaviour 390 known as thigmotaxis (Lamprea et al, 2008), allowing the assessment of the potential 391 stimulant, depressant or anxiolytic effects of a given compound (Prut and Belzung, 392 2003).Parenteral administration of 5HT 1A agonists generally induces anxiolytic-like 393 effects in rats subject to the open field tests, although non-specific 5-HT agonists (such 394 as DMT) were anxiogenic or had no effect in most studies (Prut and Belzung, 2003). In 395 our study, fluoxetine and ayahuasca-treated rats clearlyshowed a decrease in locomotion 396 activity, and less exploring behaviourthan controls, shown by decreasing rearing and 397 grooming (only ayahuasca groups).Fluoxetine is one of the most widely prescribed 398 antidepressant drugs worldwide, and is also approved for other mood disorders, 399 including generalized anxiety (Zou et al, 2013).…”
Section: Behaviour Tests 299mentioning
confidence: 68%
“…The behavior of avoiding the potentially dangerous central zone of an open field has previously been described in both vertebrates (Kallai et al, 2007;Lamprea et al, 2008) and flies (Besson and Martin, 2005;Lebreton and Martin, 2009;Martin, 2004). In Drosophila, this phenomenon has been referred to as centrophobism and it has been shown to be regulated, at least partially, by the mushroom bodies (Besson and Martin, 2005;Lebreton and Martin, 2009).…”
Section: Dtks: Distribution and Contribution To Locomotor Behaviormentioning
confidence: 98%
“…Thigmotaxis is a characteristic behaviour pattern of mice, consisting of a tendency to stay or move close to walls or vertical surfaces in an OF. 47,48 It is generally considered a sign of emotions correlated with anxiety and fear. 9,49,50 When an animal initially explores an enclosed space, it tends to stay in close contact with the perimeter of the space, and this tendency can be quantified by measuring either the amount of time spent in the central/ peripheral area, or the distance travelled (path length).…”
Section: Effects In Animal Modelsmentioning
confidence: 99%